Urinary tract infections in febrile children: Changing spectra of pathogenic bacteria and antibiotic susceptibilities?. (15th October 2018) - Rakhra, Jus; Williams, Gabrielle; Marais, Ben J; Craig, Jonathan C; Gunasekera, Hasantha
Abstract : Aim: To compare the spectra of pathogens causing febrile urinary tract infections (UTI) in children, treatment and antimicrobial susceptibility between 2004–2006 and 2007–2009. Methods: UTI were identified from a cohort study of febrile children younger than 5 years presenting to a large tertiary children's hospital's emergency department with febrile illnesses. We compared pathogenic profiles, antibiotic choices and susceptibilities between 2004–2006 and 2007–2009 and tested for differences using χ 2 and Fisher's exact tests. Antibiotic choice was compared with national therapeutic guideline recommendations for UTI in children (oral cotrimoxazole, cephalexin or amoxycillin‐clavulanate or intravenous gentamicin plus ampicillin). Results: There were 539 (2.71%) confirmed UTI from 19 889 febrile illnesses in 2004–2006 and 654 (2.99%) confirmed UTI from 21 846 febrile illnesses in 2007–2009. There was no difference in the frequency of the isolated pathogens by period: Escherichia coli (69.2 vs. 69.7%, P  = 0.85), Proteus mirabilis (7.9 vs. 7.2%, P  = 0.66) and Klebsiella species (6.2 vs. 4.7%, P  = 0.25). National therapeutic guideline recommendations were followed in 277 of 539 (51.4%) versus 318 of 654 (48.6%) ( P  = 0.34). Oral antibiotics were given in 20.6 versus 18.9%. There was no difference in extended spectrum beta lactamase (1.5 vs. 1.7%, P  = 0.82) or other antibiotic susceptibilities (e.g. E. coli : cotrimoxazole = 75.9 vs. 75.2%, P  = 0.8). Conclusions: Overall, approximately 3% of febrile illnesses were due to UTI, but we found no change in the spectrum of pathogens or antibiotic susceptibility patterns, including extended‐spectrum beta‐lactamase, with time. In both time periods, treatment followed therapeutic guidelines approximately half the time, and most pathogens were susceptible to oral antibiotics, but they were infrequently used.